A PILOT STUDY FOR EVALUATION OF ROLE OF B-MODE ULTRASOUND AND STRAIN ELASTOGRAPHY IN DIFFERENTIATING BENIGN AND MALIGNANT BREAST MASSES - GUPTA, SARYU; KAUR, MANPREET; KAUR, AMARJIT; BHATIA, KULDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Background: Early detection of malignant lesions is critical key stone for the successful management of breast cancer. Conventional B-mode ultrasound although could not replace the histopathology which is still gold standard, plays an important role in the diagnostic pathways by using the Breast Imaging Reporting and Data System (BIRADS) lexicon (standardized by American College of Radiology [ACR]). Although characterization of solid breast masses by sonography has improved greatly since the early 1990s, specificity remains low and a large number of biopsies result in benign diagnosis. Strain elastography and strain ratio (SR) are recent techniques which may help in increasing the specificity of ultrasound. Methods: The present study was a pilot study aimed to establish a correlation between B-mode ultrasound and strain elastography in differentiating benign and malignant breast masses and to compare the results of B- mode ultrasound and Strain Elastography with fine-needle aspiration cytology/ biopsy findings. It was a prospective study conducted in the Department of Radio-diagnosis of Rajindra Hospital, Patiala. A total of 40 patients who presented with the complaint of palpable breast lump were evaluated with B-Mode Ultrasonography (USG) and Strain elastography (using elastography score [ES] and SR). Results: The study group (40 patients with breast lumps) comprised 38 (95%) female patients and 2 (5%) male patients. Among the group 29 were benign and 11 were malignant. Fibroadenoma followed by fibrocystic disease was the most common benign pathologies and invasive ductal carcinoma followed by Ductal Carcinoma in situ was the most common malignant pathologies. Sensitivity, specificity, and diagnostic accuracy of B-Mode USG in diagnosing palpable breast lump are 72.7%, 86.2%, and 82.5%, respectively, while that of strain elastography in diagnosing palpable breast lump are 81.8%, 93.10%, and 90.0%, respectively. Using strain ratio (SR) only the sensitivity, specificity, and diagnostic accuracy was found to be 93.1%, 100%, and 95% better than B-Mode USG and shear elastography alone separately and combined. The mean SR for a benign mass is 2.00±0.97 and for a malignant mass is 5.40±1.55. Conclusion: Ultrasound elastography (using ES) has a higher sensitivity, specificity and diagnostic accuracy in differentiating benign and malignant breast masses then B mode USG (using BIRADS). Using SR alone has shown better sensitivity, specificity, and diagnostic accuracy but its standalone or in combination diagnostic application has to be followed up with further studies.